Microsporidia infection among various groups of the immunocompromised patients - Hassan, Nur Amirah; Lim, Yvonne Ai Lian; Mahmud, Rohela; Mohd-Shaharuddin, Norashikin; Wan Sulaiman, Wan Yusoff; Ngui, Romano (Malaysian Society of Parasitology and Tropical Medicine, 2018)
While information with regards to the bacterial and viral infections are commonly available among clinicians, data on parasitic infection, particularly Microsporidia among immunocompromised patient is currently lacking in Malaysia. This study was conducted to determine the prevalence of Microsporidia among a various group of immunocompromised patient. Two hundred and eighty-eight archived stool samples were examined for the presence of Microsporidia with Gram-Chromotrope Kinyoun staining method. The overall prevalence of Microsporidia was 29.2 % (84/288; 95% CI=24.2-34.5). The end-stage renal failure (ESRF) patients (32.1%) recorded the highest infection rate, followed by cancer (26.2%), human immunodeficiency virus (HIV/AIDS) (22.6%) and acute gastroenteritis (AGE) (7.1%). Meanwhile, organ transplant recipients and autoimmune disease patients recorded the lowest prevalence rate (6.0%). Other intestinal parasites were Strongyloides stercoralis, Trichuris trichiura, Ascaris lumbricoides and Cryptosporidium species. Diarrhoea was the most common symptoms among patients with microsporidiosis. The present study showed that the prevalence of Microsporidia infection was relatively high among immunocompromised patients. This finding highlighted the importance to include detection of microsporidia infection as a routine differential diagnosis in immunocompromised patients, which serves the benefit of treatment to the patients.